PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA SMP KURIKULUM 2013 PADA MATERI STATISTIKA DAN PELUANG DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH - Yurmalia, Della; Anggraini, Rini Dian; Solfitri, Titi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to develop mathematics learning device for junior high school that are Syllabus, Lesson Plan (LP) and Students Worksheet (SW) curriculum 2013 on subject statistics and probability by used problem based learning model. This research use development model by Borg and Gall modified by Sugiyono (2008). Development is done through the following steps: (1) potentials and problems; (2) data collection; (3) design products: (4) validation; (5) revision of design; (6) small group trial; (7) revision of product; (8) large group trial; and (9) revision. At the stage of potentials and problems, the researchers conducted potentials and problems analysis. Then, researcher collect the necessary materials to design learning device. Learning device that had been developed then validated by three validators and revised based on the input from validators. The valid learning device then tested in the small group trial with subjects are eight students of class VII SMP Negeri 23 Pekanbaru and revised based on input from the students. Then, tested in the large group trial with subjects are 39 students of class VII SMP Negeri 23 Pekanbaru and revised based on input from the students. Based on the data analysis and discussion can be concluded that the mathematics learning device for junior high school curriculum 2013 on subject statistics and probability by using problem based learning model are valid with value for the Syllabus is 3.39, value for the LP-1 is 3.42, value for the LP-2 is 3.41, value for the LP-3 is 3.41, value for the LP-4 is 3.40, value for the LP-5 is 3.40, value for the SW-1 is 3.38, value for the SW-2 is 3.32, value for the SW-3 is 3.32, value for the SW-4 is 3.32, value for SW-5 is 3.32, and is practical to use by students of junior high school.Key Words:Mathematics Learning Device for Junior High School, Curriculum 2013, Research and Development, Problem Based Learning, Statistics and Probability